LC-MS/MS method development and validation for the determination of cardiazol in human plasma - Drapak, I.; Zimenkovsky, B.; Perekhoda, L.; Kovalenko, S.; Logoyda, L.; Коваленко, Сергій Іванович (My University, 2019)
The main purpose of this study was to develop a simple, precise, rapid and accurate method for the quantification of cardiazol in human plasma.
Keywords: LC-MS/MS; Cardiazol; Human plasma; Validation; Pharmacokinetic studies